PEMANFAATAN QUALITY COST REPORT PADA QUALITY IMPROVEMENT PROGRAM DALAM RANGKA EFISIENSI BIAYA PRODUKSI PADA PERUSAHAAN - Wiratna; Ihda Mar’atun Solikhah (Fakultas Ekonomi Universitas 45 Surabaya, 2014)
The data analysis technique that used is the ratio of the percentage of the quality cost to the total sales so that it can be known the effectiveness of quality improvement program to the increasing of sales volume. The effectiveness of quality improvement program is starting showing the good change that is there are the increasing performances of this program by achieving percentage of the quality cost to the sales.